Pemberdayaan Kelompok Peternak Itik Melalui Inovasi Produk Telur Asin Asap dan Penguatan Manajemen Usaha - Herlina Lusiana; Firdaus Firdaus; Citra Amalia (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aims to increase the capacity of duck farmer groups Kuin Kacil through innovative smoked salted egg products and strengthened business management. The program was implemented due to the low economic added value of duck eggs marketed raw and the limited community capacity in business management and product marketing. The implementation method used a participatory approach, including field observation, program outreach, training, hands-on practice, mentoring, monitoring, and evaluation. The activity targeted household-scale duck farmer groups with the potential to develop livestock-based businesses. The results showed that the community was able to independently produce smoked salted eggs, understood product packaging and branding techniques, and began implementing simple business financial records. Furthermore, the community also gained an understanding of product marketing through social media as an effort to expand market reach. This activity had a positive impact on improving the community's skills, motivation, and independence in developing businesses based on local potential. The community service program is expected to increase product added value, strengthen the competitiveness of micro-enterprises, and encourage sustainable improvements in community welfare.